[OP.2B.02] COMPARATIVE MICRORNA PROFILING IN RELATION TO URINARY ALBUMIN EXCRETION IN NEWLY DIAGNOSED HYPERTENSIVE PATIENTS. (September 2016) - Marketou, M.; Parthenakis, F.; Kontaraki, J.; Maragoudakis, F.; Maragkoudakis, S.; Nakou, H.; Roufas, K.; Patrianakos, A.; Logakis, J.; Vougia, D.; Malliaraki, N.; Vardas, P.
Abstract : Objective: Microalbuminuria is an established early marker of endothelial dysfunction and damage. MicroRNAs are emerging as essential modulators of cardiovascular physiology and disease. In the present study, we sought an association between the differential expression of related microRNAs in the peripheral blood mononuclear cells of untreated patients with newly diagnosed essential hypertension and levels of urinary albumin excretion. Design and method: We assessed the expression of the microRNAs miR-1, miR-133a, miR-26b, miR-208b, miR-499, and miR-21 in consecutive subjects with untreated newly diagnosed essential hypertension (aged 62.5 ± 9.7 years) and with no indications of other organic heart disease. MicroRNA expression levels in peripheral blood mononuclear cells were quantified by real-time reverse transcription polymerase chain reaction. Results: The prevalence of microalbuminuria was 9.8%. MiRNA-208b and miRNA-133a were independently correlated with 24-h urinary albumin excretion. More specifically, a strong association was found between the gene expression levels of miRNA-208b in our patients' peripheral blood cells and urinary albumin (r = 0.72, p < 0.001). A similar association was found for miRNA-133a (r = 0.372, p < 0.001). Conclusions: In conclusion, miRNA-208b and miRNA-133a show distinct profiling in peripheral blood cells isolated from untreated patients with recently diagnosed essential hypertension. Their gene expression levels reveal a strong correlation with urinary albumin excretion levels. Our findings provide new perspectives on the development of a new generation of biomarkers for the better monitoring of end-organ damage in hypertension.